Análisis de la influencia de las redes sociales (Whatsapp, messenger) en la destreza de redacción de los estudiantes de primer semestre de Comunicación Social de la Universidad Técnica de Babahoyo - Sosa Vélez, Bryan Martin (2020)
Writing was born as a needed and was developed to be considered an art, despite being one of engine for human growth, these matured and coupled with certain technologies are degrading the style and way of communicating. The XXI century, communication boom allowed users to express their ideas immediately through the instant messaging applications or better known as social networks. On the other hand, the language has been affected by the artificial intelligence offered by the technology, which has facilitated the corrections of spelling errors. However, despite its operation there are many shortcomings and flaws in writing that can only be overcome through knowledge and practice. The paper offers a brief overview of writing influenced by social media and its effect on students writing skills in the initial stage of the Communication Career.